Exploring the forest - poverty link - Center for International Forestry Research (Center for International Forestry Research, 2003)
This infobrief provides key points that in exploring the link from forests to poverty alleviation, two key questions arise: What role can forests and forestry play in the efforts to reduce poverty in developing countries? And to what extent do forests help prevent extreme hardship, even when they don’t reduce poverty? A striking gap exists between, on the one hand, the neglect of forests in economic development and poverty reduction strategies and on the other, the high (and sometimes unrealistic) expectations regarding the role for forest products in parts of the forest literature. From a macro-level perspective, economic growth normally does trickle down to the poor, at least over time and at aggregate scales. The forest literature tends to ignore this effect, including the impact of forest rents flowing into other sectors. Non-timber forest products (NTFPs) serve subsistence needs, can have important ‘gap filling’ fnctions and sometimes provide regular cash income. However, there is a strong association between poverty and NTFP dependence. Paradoxically, the same characteristics that make NTFPs important and attractive to the poor, also limit their potential for increasing incomes. Timber has traditionally been the rich man’s lot but the current trends of increased local control over natural forests, smallholder tree growing and small scale, wood-based enterprises may somewhat modify this picture. The realm of payments for ecological services is expanding rapidly and has a huge potential but the extent to which the poor will benefit remains uncertain. The choices relating to livelihood and poverty definitions, concepts and indicators clearly influence policy and project design, as well as research results and interpretations. Particularly promising topics for future study are identified within the fields of: assessing current forest-based benefits to the poor; exploring emerging market opportunities; and evaluating cross-cutting institutional and extra-sectoral issues.